Interaksi Nisbah Daun: Buah dan Pupuk Daun pada Kualitas Buah Abiu (Pouteria caimito Radlk.) - Aria Thamara; Slamet Susanto; Deden Derajat Matra; Winarso Drajad Widodo (Jurnal Ilmu Pertanian Indonesia, 2024)
Abiu (Pouteria caimito Radlk.) is a plant of Sapotaceae family that can be consumed fresh, processed, or as a medical product. The fruit and leaves of this plant contain bioactive compounds. This research aims to inform the interaction between leaf:fruit ratio treatment and foliar fertilizer on the quality of the abiu fruit. The study was conducted at Kebun Balungbang Jaya, Dramaga, Bogor, West Java Province, from July 2022 to November 2022. The experiment used a factorial split plot design. The main plot was a leaf:fruit ratio treatment (N1, 45 leaves:1 fruit, and N2, 30 leaves:1 fruit) on each tertiary branch, and the tiller plot was foliar fertilizer (P1: 1 g L-1, P2: 2 g L-1, and P3: 3 g L-1), which consisted of 3 replications. The results showed that treatment of the leaf-fruit ratio and foliar fertilizer did not affect the quality of the abiu fruit. The interaction between leaf:fruit ratio and foliar fertilizer had a significant effect on ATT, as indicated by the lowest acidity value in the leaf:fruit ratio treatment of 45:1 and a fertilizer concentration of 1 g L-1 with a value of 0.12% but has no significant effect on the external and internal quality of other fruits. Keywords: Bioactive compounds, sapotaceae, tertiary branch, titratable acidity